Victim, perpetrator, or what else? : generational and gender perspectives on children, youth, and violence - Bühler-Niederberger, Doris; Alberth, Lars (Bingley, U.K. : Emerald Publishing Limited, 2019)
Children, while being the most victimised group in society, rarely become a topic of sociological research, neither as victims nor as perpetrators. The sociological discussion on power and violence happens beyond generation as an important dimension of social structure, and in many respects also beyond gender aspects that are inseparably linked to generational violence. This is a severe omission when the extent of violence in a society needs to be understood, as well as the structures and processes perpetuating violence or opposing its abolition. It is also a serious obstacle when understanding the position of children and exploring the social meaning of childhood. This volume addresses this blind spot in sociology. It does so by mapping the ways that children and young people are considered victims or perpetrators by their societies and consequently the ways that their societies react. The chapters analyse a variety of phenomena in different countries of the Global North and South. All of these phenomena may be considered to include acts of violence toward children and adolescents, or those committed by them. Thus, violence is addressed as one of the major building blocks of the scope and qualities of children's agency, limiting the social recognition of their rights as members of their respective societies. With a global reach and cutting-edge research, this book will prove an invaluable text for researchers and leaders in the fields of comparative childhood research and sociology of violence alike.
Part I: Perceptions and definitions -- Chapter 1. The rhetorical idiom of unreason: on labeling in child protection / Lars Alberth -- Chapter 2. The Perpetration of Fatal Child Maltreatment: It's the Men Who Are Bad, Right? Emily M. Douglas and Kerry A. Lee -- Chapter 3. The Definitions Are Legion: Academic Views and Practice Perspectives On Violence Against Children / Andreas Jud and Peter Voll -- Chapter 4. Putting Definitions to Work: Reflection From The Canadian Domestic Homicide Prevention Initiative With Vulnerable Populations / Jordan Fairbairn, Danielle Sutton, Myrna Dawson and Peter Jaffe -- Part II: Institutional Reactions -- Chapter 5. Naughty Or Bad: Children And Crime / Robert van Krieken -- Chapter 6. Perceptions Of Violence Within Child Protection Systems In Russia: Views Of Children, Parents, And Social Workers / Veronika Odinokova, Maia Rusakova and Vladlena Avdeeva -- Part III: Conditions of Change: Global, National and Local -- Chapter 7. Exploring the Role of Gender Norms In Shaping Adolescents' Experiences Of Violence In Pastoralist Afar / Ethiopia / Nicola Jones, Yitagesu Gebeyeh, and Joan Hamory Hicks -- Chapter 8. Governing Childhood in India: The Up-Hill Battle to Abolish Child Marriage / Elvira Graner -- Chapter 9. Child Marriage in Kyrgyzstan: Exploring Institutional Ambivalences in Constructing The "Victim" / Elena Kim -- Chapter 10. Child Marriage and Sexual Violence in The United States / Jamie O'Quinn.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Abused children -- Social aspects; Abused children -- Social conditions; Child abuse -- Social aspects; Victims of family violence -- Social conditions; Family violence -- Social aspects; Juvenile delinquency; Social Science -- Children's Studies; Child abuse